3D printing state high-strength and high-corrosion-resistance magnesium alloy and preparation method and application thereof
By adding specific elements to the magnesium alloy, a 3D-printed high-strength, high corrosion resistance magnesium alloy is designed, which solves the problem that 3D-printed magnesium alloys in the prior art is difficult to take into account both mechanical properties and corrosion properties, and realizes the high-performance magnesium alloy used in automotive applications.
Patent Information
- Application Number
- CN202411789627.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-06
- Publication Date
- 2025-03-11
AI Technical Summary
In the prior art, 3D printed magnesium alloys are difficult to take into account both high strength and high corrosion resistance, which affects their widespread use in automotive applications.
By adding elements such as Sn, Zr, Gd, Nd and Zn to the magnesium alloy, a 3D-printed high-strength, high corrosion resistance magnesium alloy is designed. The synergistic effect of these elements is used to form a small and evenly distributed precipitation phase to improve the strength and corrosion resistance of the alloy.
It realizes the unity between mechanical properties and corrosion properties of 3D printed magnesium alloys, and has high strength and high corrosion resistance comparable to cast magnesium alloys, and is suitable for automobile manufacturing.
Smart Images

Figure CN119592856A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of magnesium alloys, and in particular relates to a 3D printed high-strength and high-corrosion-resistant magnesium alloy and a preparation method and application thereof. Background Art
[0002] Magnesium alloy is the lightest metal structural material with a density of only 1.74g / cm 3 , the widespread use of magnesium alloys can significantly reduce the weight of the structural parts themselves, and has an important contribution to achieving lightweight electric vehicles, especially mileage issues. 3D printing is also used as an emerging technology to manufacture complex samples such as stainless steel, titanium alloys, and aluminum alloys, and has been successfully used in engine cases, heat dissipation ducts, and weight-reducing structural parts. The application of 3D printed magnesium alloys in automobiles has been gradually carried out. Aiming at the actual service environment of automobiles, 3D printed magnesium alloys can be used for the production of precision automotive parts, greatly saving time and labor costs. However, due to problems with the 3D printing process, its corrosion resistance and mechanical properties are often difficult to take into account. This has greatly affected the application of 3D printed magnesium alloys in automobiles.
[0003] The Chinese invention patent application with the publication number "CN117431443A" and the title "A high-strength and corrosion-resistant magnesium alloy bar and its preparation method" discloses a corrosion-resistant, high-strength and plastic magnesium alloy. By adding trace amounts of rare earth elements gadolinium (Gd), yttrium (Y) and other trace metal elements zinc (Zn) and manganese (Mn), the stability and density of the corrosion product film are improved, the corrosion of chloride ions on the alloy surface is hindered, local corrosion is inhibited, and the corrosion resistance of the alloy is improved. In addition, the preparation method disclosed in the comparative document refines the grain size, improves the mechanical properties and corrosion resistance through fine grain strengthening and solid solution strengthening, and thus successfully prepares a corrosion-resistant, high-strength and plastic magnesium alloy.
[0004] A Chinese invention patent application with publication number "CN117230354A" and title "A high-strength and tough rare earth magnesium alloy wire for additive manufacturing and its preparation method" discloses a magnesium alloy whose composition is Mg-aGd-bY-cCa-dAl, wherein 4.0wt.%≤a≤9.5wt.%, 2.0wt.%≤b≤4.0wt.%, 1.0wt.%≤c≤2.5wt.%, 0.5wt.%≤d≤1.2wt.%. The comparative document discloses that by adding rare earth elements to pure magnesium, the corrosion of magnesium alloys can be reduced and the discharge efficiency of magnesium alloys can be improved. At the same time, the addition of rare earth elements produces a good solid solution strengthening effect, which improves the strength of magnesium alloys. In addition, during the additive manufacturing process, the magnesium matrix will dynamically precipitate MgxGd and MgxY precipitation phases, and the strength of the magnesium alloy will be improved through precipitation strengthening.
[0005] However, none of the above existing technologies have achieved the unification of corrosion resistance and mechanical properties of additively manufactured magnesium alloys. There is a continuous need in the art to develop 3D printed magnesium alloys with high corrosion resistance and good mechanical properties suitable for automotive casting processes. Summary of the invention
[0006] In order to solve the problem in the prior art that it is difficult for 3D printed magnesium alloys to have both good mechanical properties and corrosion properties, the present invention proposes a 3D printed high-strength and high-corrosion-resistant magnesium alloy and a preparation method and application thereof.
[0007] To achieve the above object, the present invention provides the following technical solutions:
[0008] Technical solution 1: A 3D printed high-strength and high-corrosion-resistant magnesium alloy, comprising the following components in mass percentage: Sn: 0.1-0.6%, Zr: 0.1-0.5%, Gd: 0.5-0.9%, Nd: 2.8-3.5%, Zn: 0.1-0.3%, and the balance is Mg and unavoidable impurities.
[0009] The 3D printed high-strength and high-corrosion-resistant magnesium alloy includes a matrix phase and a second precipitated phase with a quasi-network distribution, wherein the elements contained in the second precipitated phase are MgNdZr and NdGd.
[0010] The addition of Nd and Gd will disrupt the regular arrangement of magnesium lattice and increase the resistance of dislocation movement, thereby improving the yield strength and hardness of the material; the addition of Zr and rare earth elements Nd, Gd, Sn can be used as grain refiners to reduce the grain size of the alloy. Smaller grain size can improve the yield strength and toughness of the alloy, because grain boundaries can hinder the movement of dislocations, thereby enhancing the strength of the material; Nd, Gd, Sn can form fine and evenly distributed precipitates during aging treatment, which can effectively hinder the movement of dislocations, thereby improving the strength and hardness of the alloy; Sn element can slightly enhance the corrosion resistance by improving the potential difference between the matrix and the second phase, while Zn element can improve the corrosion resistance by improving the surface state of the alloy or forming a passivation film with self-healing properties; Nd, Gd and Sn rare earth elements have a significant limiting effect on the diffusion of Cl ions, making the film layer have better corrosion resistance; The addition of Zn element can generate strengthening phases with other alloys, while the addition of Zr element can promote the generation of fine grain strengthening and improve the strength of the material. In summary, after the synergistic effect of all elements, a 3D printed high-strength and high-corrosion-resistant magnesium alloy with both mechanical properties and corrosion properties is obtained.
[0011] Preferably, the 3D printed high-strength and high-corrosion-resistant magnesium alloy comprises the following components in mass percentage: Sn: 0.2-0.3%, Zr: 0.1-0.2%, Gd: 0.8-0.9%, Nd: 2.9-3.0%, Zn: 0.2-0.3%, and the remainder is Mg and unavoidable impurities.
[0012] More preferably, the 3D printed high-strength and high-corrosion-resistant magnesium alloy includes the following components in mass percentage: Sn: 0.24%, Zr: 0.19%, Gd: 0.89%, Nd: 2.91%, Zn: 0.21%, and the balance is Mg and unavoidable impurities.
[0013] Preferably, the unavoidable impurities include Fe, and the Fe content is ≤0.05%.
[0014] Technical Solution 2: A method for preparing a 3D printed high-strength and high-corrosion-resistant magnesium alloy, comprising the following steps:
[0015] The components are weighed according to mass percentage to cast into a magnesium alloy ingot, the magnesium alloy ingot is subjected to heat treatment and then cold water quenching to obtain a cast magnesium alloy; the cast magnesium alloy is subjected to wire drawing and melted for additive manufacturing to obtain a 3D printed high-strength and high-corrosion-resistant magnesium alloy.
[0016] Preferably, the heat treatment parameters are: temperature 530-540° C., time 7-9 h.
[0017] Preferably, the melting parameters are: temperature 900-1000° C., time 11-13 h.
[0018] Technical Solution 3: Application of a 3D printed high-strength and high-corrosion-resistant magnesium alloy in the field of automobile manufacturing. The self-repairing and high-corrosion-resistant ternary magnesium alloy prepared by the method of the present invention has a hydrogen evolution corrosion rate of less than 1.3 ml / cm in an immersion environment. 2 *day.
[0019] Compared with the prior art, the present invention has the following advantages and technical effects:
[0020] The present invention incorporates Nd, Gd, Sn, Zr and Zn into the magnesium alloy, and solves the problem in the prior art that the 3D printed magnesium alloy is difficult to have both high strength and high corrosion resistance comparable to the cast state by designing the 3D printed high-strength and high-corrosion-resistant magnesium alloy. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] The accompanying drawings constituting a part of the present invention are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the accompanying drawings:
[0022] Figure 1 This is a scanning electron microscope image of the 3D printed high-strength and high-corrosion-resistant magnesium alloy prepared in Example 1;
[0023] Figure 2 This is a cross-sectional morphology of the 3D printed high-strength and high-corrosion-resistant magnesium alloy prepared in Example 1 after the corrosion test;
[0024] Figure 3 This is a scanning electron microscope image of the 3D printed magnesium alloy before aging treatment in Scheme 10;
[0025] Figure 4 This is a scanning electron microscope image of the 3D printed magnesium alloy after aging treatment in Example 3. DETAILED DESCRIPTION
[0026] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0027] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0028] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0029] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.
[0030] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0031] The present invention provides a 3D printed high-strength and high-corrosion-resistant magnesium alloy, comprising the following components in mass percentage: Sn: 0.1-0.6%, Zr: 0.1-0.5%, Gd: 0.5-0.9%, Nd: 2.8-3.5%, Zn: 0.1-0.3%, and the balance is Mg and inevitable impurities.
[0032] In the following preferred embodiments of the present invention, the 3D printed high-strength and high-corrosion-resistant magnesium alloy contains 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6% or any range or sub-range between the aforementioned ratios of Sn, preferably 0.2-0.3%.
[0033] In the following preferred embodiments of the present invention, the 3D printed high-strength and high-corrosion-resistant magnesium alloy contains 0.1%, 0.2%, 0.3%, 0.4%, 0.5% or any range or sub-range between the aforementioned ratios of Zr, preferably 0.1-0.2%.
[0034] In the following preferred embodiments of the present invention, the 3D printed high-strength and high-corrosion-resistant magnesium alloy contains 0.5%, 0.6%, 0.7%, 0.8%, 0.9% or any range or sub-range between the aforementioned ratios of Gd, preferably 0.8-0.9%.
[0035] In the following preferred embodiments of the present invention, the 3D printed high-strength and high-corrosion-resistant magnesium alloy contains 2.8%, 2.9%, 3.0%, 3.1%, 3.2%, 3.3%, 3.4%, 3.5% or any range or sub-range between the aforementioned ratios of Nd. Preferably, it contains 2.9-3.0% Nd.
[0036] In the following preferred embodiments of the present invention, the 3D printed high-strength and high-corrosion-resistant magnesium alloy contains 0.1%, 0.2%, 0.3% or any range or sub-range between the aforementioned ratios of Zn, preferably 0.2-0.3%.
[0037] Based on the above-mentioned preferred components, the 3D printed high-strength and high-corrosion-resistant magnesium alloy preferably includes the following components in mass percentage: Sn: 0.2-0.3%, Zr: 0.1-0.2%, Gd: 0.8-0.9%, Nd: 2.9-3.0%, Zn: 0.2-0.3%, and the balance is Mg and unavoidable impurities.
[0038] More preferably, the composition includes the following mass percentages: Sn: 0.24%, Zr: 0.19%, Gd: 0.89%, Nd: 2.91%, Zn: 0.21%, and the balance is Mg and inevitable impurities.
[0039] Wherein, the unavoidable impurities include Fe, and the Fe content is ≤0.05%.
[0040] The method for preparing the 3D printed high-strength and high-corrosion-resistant magnesium alloy comprises the following steps:
[0041] (1) Casting a magnesium alloy ingot according to a conventional casting process;
[0042] (2) placing the magnesium alloy ingot into a high temperature furnace for heat treatment, and then quenching with cold water to obtain a cast magnesium alloy;
[0043] (3) The cast magnesium alloy is drawn and then melted for additive manufacturing to obtain a 3D printed high-strength and high-corrosion-resistant magnesium alloy.
[0044] In the following preferred embodiments of the present invention, the parameters of the heat treatment in step (2) are: temperature 530-540° C., time 7-9 h. For example, the heat treatment is performed at a temperature of 535° C. and a time of 8 h in the following embodiments of the present invention.
[0045] In the following preferred embodiments of the present invention, the parameters of the melting in step (2) are: temperature 900-1000° C., time 11-13 h. For example, in the following embodiments of the present invention, the heat treatment is performed at a temperature of 950° C. and a time of 12 h.
[0046] In the process of preparing 3D printed high-strength and high-corrosion-resistant magnesium alloys of the present invention, except for the limitations of heat treatment and melting parameters, other processes can adopt conventional methods. Therefore, the conventional processes and parameters are not specifically limited in the following embodiments. To maintain uniformity, the parameters in different tests can be kept consistent.
[0047] The application of the 3D printed high-strength and high-corrosion-resistant magnesium alloy in the field of automobile manufacturing. Preferably, the automobile is an electric car. The application may include solid solutionizing the 3D printed high-strength and high-corrosion-resistant magnesium alloy as described in the present invention, recasting it, and then adding materials after drawing to obtain the required automobile materials. The high-corrosion-resistant ternary magnesium alloy with self-healing properties prepared by the method of the present invention has a hydrogen evolution corrosion rate of less than 1.3 ml / cm in an immersion environment. 2 *day.
[0048] As an additional embodiment, the present invention also provides a heat treatment optimization method for 3D printed magnesium alloy, comprising the following steps:
[0049] (1) Preheating a heat treatment furnace to 535° C., placing the 3D printed high-strength and high-corrosion-resistant magnesium alloy in the furnace for solution treatment, the solution treatment temperature is 535° C., and the temperature is kept for 8 hours, and then the alloy is placed in cold water and cooled to room temperature;
[0050] (2) Preheating the heat treatment furnace to 200° C., placing the 3D printed high-strength and high-corrosion-resistant magnesium alloy processed in step (1) in the furnace for aging treatment, the aging treatment temperature is 200° C., and the temperature is kept for 16 hours. Then, the alloy is placed in cold water and cooled to room temperature to obtain the final alloy product.
[0051] In the heat treatment optimization method, the present invention adopts the T6 heat treatment process, that is, the state of artificial aging after solid solution, the solid solution parameters are selected as 535°C and 8h, and the artificial aging temperature is selected as 200°C and 16h. The mechanical properties and corrosion resistance of the obtained 3D printed magnesium alloy are greatly improved compared with the mechanical properties and corrosion resistance of the 3D printed magnesium alloy that has not been heat treated and other 3D printed magnesium alloys of the T6 heat treatment process. At the same time, the organization of the 3D printed magnesium alloy before and after the heat treatment is compared. It is found that the net-like second phase on the grain boundary after the heat treatment is significantly reduced, and the total amount of the second phase is significantly reduced. The reduction of the second phase weakens the micro-galvanic corrosion and improves the corrosion performance. At the same time, the mechanical properties are strengthened by the aging treatment. A 3D printed magnesium alloy with ideal strength and corrosion resistance is achieved through a heat treatment process.
[0052] In the following preferred embodiments of the present invention, the 3D printed high-strength and high-corrosion-resistant magnesium alloy includes the following components in mass percentage: Sn: 0.1-0.6%, Zr: 0.1-0.5%, Gd: 0.5-0.9%, Nd: 2.8-3.5%, Zn: 0.1-0.3%, and the balance is Mg and unavoidable impurities.
[0053] In the following preferred embodiments of the present invention, the 3D printed high-strength and high-corrosion-resistant magnesium alloy contains 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6% or any range or sub-range between the aforementioned ratios of Sn, preferably 0.2-0.3%.
[0054] In the following preferred embodiments of the present invention, the 3D printed high-strength and high-corrosion-resistant magnesium alloy contains 0.1%, 0.2%, 0.3%, 0.4%, 0.5% or any range or sub-range between the aforementioned ratios of Zr, preferably 0.1-0.2%.
[0055] In the following preferred embodiments of the present invention, the 3D printed high-strength and high-corrosion-resistant magnesium alloy contains 0.5%, 0.6%, 0.7%, 0.8%, 0.9% or any range or sub-range between the aforementioned ratios of Gd, preferably 0.8-0.9%.
[0056] In the following preferred embodiments of the present invention, the 3D printed high-strength and high-corrosion-resistant magnesium alloy contains 2.8%, 2.9%, 3.0%, 3.1%, 3.2%, 3.3%, 3.4%, 3.5% or any range or sub-range between the aforementioned ratios of Nd. Preferably, it contains 2.9-3.0% Nd.
[0057] In the following preferred embodiments of the present invention, the 3D printed high-strength and high-corrosion-resistant magnesium alloy contains 0.1%, 0.2%, 0.3% or any range or sub-range between the aforementioned ratios of Zn, preferably 0.2-0.3%.
[0058] Based on the above-mentioned preferred components, the 3D printed high-strength and high-corrosion-resistant magnesium alloy preferably includes the following components in mass percentage: Sn: 0.2-0.3%, Zr: 0.1-0.2%, Gd: 0.8-0.9%, Nd: 2.9-3.0%, Zn: 0.2-0.3%, and the balance is Mg and unavoidable impurities.
[0059] More preferably, the composition includes the following mass percentages: Sn: 0.24%, Zr: 0.19%, Gd: 0.89%, Nd: 2.91%, Zn: 0.21%, and the balance is Mg and inevitable impurities.
[0060] Wherein, the unavoidable impurities include Fe, and the Fe content is ≤0.05%.
[0061] The raw material 3D printed high-strength and high-corrosion-resistant magnesium alloy used in the heat treatment optimization method can be prepared by any conventional method. In the following embodiments of the present invention, the raw material 3D printed high-strength and high-corrosion-resistant magnesium alloy required in the heat treatment optimization process is prepared by the above-mentioned preparation method of the 3D printed high-strength and high-corrosion-resistant magnesium alloy.
[0062] The "heat treatment process using T6" described in the present invention refers to the process of "solution treatment + complete artificial aging".
[0063] The "room temperature" mentioned in the present invention, unless otherwise specified, is 20-30°C.
[0064] The raw materials used in the present invention are all purchased from the market.
[0065] The technical solution of the present invention is further illustrated by the following embodiments.
[0066] Example 1
[0067] A 3D printed high-strength and high-corrosion-resistant magnesium alloy includes the following components in mass percentage: Sn: 0.24%, Zr: 0.19%, Gd: 0.89%, Nd: 2.91%, Zn: 0.21%, the remainder being Mg and impurity Fe, and the Fe content is ≤0.05%.
[0068] The preparation method comprises the following steps:
[0069] (1) Weighing the above components by mass percentage and casting them into magnesium alloy ingots according to conventional casting process;
[0070] (2) placing the magnesium alloy ingot in a high temperature furnace for heat treatment at 535° C. for 8 h, and then quenching in cold water to obtain a cast magnesium alloy;
[0071] (3) The cast magnesium alloy was drawn and melted at 950°C for 12 h for additive manufacturing to obtain a 3D printed high-strength and high-corrosion-resistant magnesium alloy.
[0072] Example 2
[0073] A 3D printed high-strength and high-corrosion-resistant magnesium alloy includes the following components in mass percentage: Sn: 0.48%, Zr: 0.18%, Gd: 0.50%, Nd: 3.24%, Zn: 0.25%, the remainder being Mg and impurity Fe, and the Fe content is ≤0.05%.
[0074] The preparation method is the same as that of Example 1.
[0075] Comparative Example 1
[0076] A cast magnesium alloy comprises the following components in mass percentage: Sn: 0.27%, Zr: 0.22%, Gd: 0.83%, Nd: 2.97%, Zn: 0.19%, the balance being Mg and impurity Fe, and the Fe content is ≤0.05%.
[0077] The preparation method comprises the following steps:
[0078] (1) Weighing the above components by mass percentage and casting them into magnesium alloy ingots according to conventional casting process;
[0079] (2) The magnesium alloy ingot was placed in a high temperature furnace for heat treatment at 535°C for 8 h, and then quenched in cold water to obtain a cast magnesium alloy.
[0080] Comparative Example 2
[0081] A 3D printed high-strength and high-corrosion-resistant magnesium alloy includes the following components in mass percentage: Sn: 0.01%, Zr: 0.02%, Gd: 1.25%, Nd: 2.58%, Zn: 0.02%, the remainder is Mg and impurity Fe, and the Fe content is ≤0.05%.
[0082] The preparation method is the same as Example 1.
[0083] Performance Testing:
[0084] 1. The magnesium alloys prepared in Example 1-2 and Comparative Example 1-2 were observed and photographed under a scanning electron microscope. The results are as follows: Figure 1 shown. Figure 1 The medium grey is the magnesium alloy matrix phase, and the white is the precipitation phase. It can be seen that the second phase with a quasi-network distribution can form a corrosion barrier to improve the corrosion performance of the matrix.
[0085] 2. Determination of degradation rate in simulated body fluids: Determination of degradation rate in simulated body fluids according to ASTM-G31-72 "Laboratory immersion corrosion test for metals". The magnesium alloy samples prepared in Example 1-2 and Comparative Example 1-2 were immersed in a 3.5% by mass NaCl solution for 96 hours to obtain the following hydrogen evolution and weight loss data.
[0086] Table 1
[0087]
[0088] The cross-sectional morphology of the 3D printed high-strength and high-corrosion-resistant magnesium alloy of Example 1 after the immersion test was observed by electron microscopy ( Figure 2 ).
[0089] Figure 1 and Figure 2 The scanning electron microscope model used is: RISE-MAGNA. The specific sample preparation process and test conditions are: polishing with sandpaper to 7000#, then observing after alcohol cleaning. Figure 1 The test conditions are 5keV SE mode, Figure 2 The test condition is 20keV BSE mode.
[0090] 3. Electrochemical testing of magnesium alloys prepared in Example 1-2 and Comparative Example 1-2: The tests were conducted on an autolab 300 in accordance with GBT 24196-2009 “Corrosion of metals and alloys. Electrochemical test methods. Guide for constant potential and dynamic potential polarization measurements”. The results are shown in Table 2.
[0091] Table 2 Electrochemical performance test results of magnesium alloy
[0092]
[0093] 4. Mechanical property test of magnesium alloy prepared in Example 1-2 and Comparative Example 1-2: The test was carried out using a C45.504Y microcomputer-controlled electronic universal testing machine in strict accordance with the standard of "Metallic Material Tensile Test Part 1: Room Temperature Test Method GB / T228.1-2010". The results are shown in Table 3.
[0094] Table 3 Mechanical properties test results of magnesium alloy
[0095]
[0096] It can be seen from Tables 1 to 3 that the corrosion rate of the magnesium alloy prepared by the method of Example 1 in the immersion environment is less than 1.3 ml / cm 2 *day, the minimum weight loss rate can reach 1.65mg / cm 2 *day.
[0097] Compared with Example 2, Example 1 shows that the corrosion rate fluctuates slightly with the change of Sn, Gd and Nd contents, but the change is not obvious. This shows that under this composition condition, the change of the composition of several elements cannot significantly change the corrosion rate, but a slight increase in the amount of precipitated phase will affect the corrosion resistance.
[0098] Compared with Comparative Example 1, when the composition of the cast magnesium alloy of Comparative Example 1 is similar to the composition of the 3D printed high-strength and high-corrosion-resistant magnesium alloy of Example 1, its corrosion performance and mechanical properties are significantly lower than those of the 3D printed high-strength and high-corrosion-resistant magnesium alloy.
[0099] Compared with Example 1 and Comparative Example 2, the corrosion performance and mechanical properties of the 3D printed high-strength and high-corrosion-resistant magnesium alloy prepared in Comparative Example 2 are significantly lower than those of the 3D printed high-strength and high-corrosion-resistant magnesium alloy in Example 1.
[0100] Example 3
[0101] A heat treatment optimization method for 3D printed magnesium alloy, comprising the following steps:
[0102] (1) Preheating a heat treatment furnace to 535° C., placing the 3D printed magnesium alloy prepared in Example 1 in the furnace for solution treatment, the temperature of the solution treatment is 535° C., keeping the temperature for 8 h, and then placing it in cold water to cool to room temperature;
[0103] (2) Preheating the heat treatment furnace to 200° C., placing the 3D printed magnesium alloy processed in step (1) in the furnace for aging treatment, the aging treatment temperature is 200° C., and the temperature is kept for 16 hours. Then, the alloy is placed in cold water and cooled to room temperature to obtain the final alloy product.
[0104] Ten different aging schemes are established below to optimize the heat treatment route and parameters of the present invention, as shown in Table 4. Scheme 4 is the parameters of the aging treatment in Example 3, and the other schemes are schemes obtained by changing the aging temperature and time on the basis of Scheme 4 and the initial 3D printed magnesium alloy that has not been heat treated, which is the comparative example (Scheme 10). In addition, the other process parameters outside Table 4 are the same as those in Example 3. The strength indexes of the magnesium alloys obtained by using the 10 schemes are shown in Table 5, and the corrosion resistance indexes of the magnesium alloys obtained by using the 10 schemes are shown in Table 6.
[0105] The scanning electron microscope images of the 3D printed magnesium alloy without aging treatment in Scheme 10 and the 3D printed magnesium alloy after aging treatment prepared in Scheme 4 are as follows Figure 3 and Figure 4 As shown. Figure 3 and Figure 4 It can be seen that after heat treatment, the network-like second phase on the grain boundary is significantly reduced, and the total amount of the second phase is significantly reduced.
[0106] Table 4 Comparison of aging treatment in different implementation schemes
[0107]
[0108] Table 5 Comparison of tensile properties of different implementation schemes
[0109]
[0110] Table 6 Comparison of corrosion resistance of different implementation schemes
[0111]
[0112] According to Table 4 and Table 5, comparing Schemes 1-10, it can be found that the mechanical properties of the 3D printed magnesium alloy in Scheme 4 are significantly improved compared with other schemes.
[0113] According to Table 4 and Table 6, by comparing Schemes 1-10, it can be found that Schemes 1-9 have greatly improved corrosion resistance compared with Scheme 10, that is, the 3D printed magnesium alloy after heat treatment has better corrosion resistance than the 3D printed magnesium alloy without heat treatment. However, by comparing Schemes 1-9, the difference in corrosion resistance between different schemes is not large. Combined with the mechanical property data in Table 5, it is concluded that the 3D printed magnesium alloy after heat treatment in Scheme 4 has the best mechanical properties and corrosion resistance.
[0114] The above are only preferred specific embodiments of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed by the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.
Claims
1. A 3D printed high-strength and high-corrosion-resistant magnesium alloy, characterized in that: The present invention comprises the following components in mass percentage: Sn: 0.1-0.6%, Zr: 0.1-0.5%, Gd: 0.5-0.9%, Nd: 2.8-3.5%, Zn: 0.1-0.3%, and the balance is Mg and inevitable impurities.
2. The 3D printed high-strength and high-corrosion-resistant magnesium alloy according to claim 1, characterized in that: The present invention comprises the following components in mass percentage: Sn: 0.2-0.3%, Zr: 0.1-0.2%, Gd: 0.8-0.9%, Nd: 2.9-3.0%, Zn: 0.2-0.3%, and the balance is Mg and inevitable impurities.
3. The 3D printed high-strength and high-corrosion-resistant magnesium alloy according to claim 2, characterized in that: The alloy comprises the following components in mass percentage: Sn: 0.24%, Zr: 0.19%, Gd: 0.89%, Nd: 2.91%, Zn: 0.21%, and the balance is Mg and inevitable impurities.
4. The 3D printed high-strength and high-corrosion-resistant magnesium alloy according to claims 1-3, characterized in that: The unavoidable impurities include Fe, and the Fe content is ≤0.05%.
5. A method for preparing a 3D printed high-strength and high-corrosion-resistant magnesium alloy according to any one of claims 1 to 4, characterized in that: The following steps are involved: The components are weighed according to mass percentage to cast into a magnesium alloy ingot, the magnesium alloy ingot is subjected to heat treatment and then cold water quenching to obtain a cast magnesium alloy; the cast magnesium alloy is subjected to wire drawing and melted for additive manufacturing to obtain a 3D printed high-strength and high-corrosion-resistant magnesium alloy.
6. The method for preparing a 3D printed high-strength and high-corrosion-resistant magnesium alloy according to claim 5, characterized in that: The parameters of the heat treatment are: temperature 530-540° C., time 7-9 h.
7. The method for preparing a 3D printed high-strength and high-corrosion-resistant magnesium alloy according to claim 5, characterized in that: The melting parameters are: temperature 900-1000° C., time 11-13 h.
8. Application of the 3D printed high-strength and high-corrosion-resistant magnesium alloy according to any one of claims 1 to 4 in the field of automobile manufacturing.
Citation Information
Patent Citations
High-strength and high-toughness rare earth magnesium alloy wire for additive manufacturing and preparation method of high-strength and high-toughness rare earth magnesium alloy wire
CN117230354A
High-strength corrosion-resistant magnesium alloy bar and preparation method thereof
CN117431443A